UNCITRAL and the enforceability of iMSAs: the debate heats up – Part 3 - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2016)
This is the third of four in a series of blog posts on Kluwer Mediation Blog. They were published in conjunction with the the 65th session of the UNCITRAL Working Group II on arbitration and conciliation. The Working Group has turned its attention to the settlement of commercial disputes and in particular on the preparation of an instrument on the enforcement of international commercial settlement agreements resulting from conciliation. (Note that in UNCITRAL speak, the term ‘conciliation’ is used interchangeably with ‘mediation’. ) In terms of the type of instrument, the Working Group is considering the possibility of a convention, model provisions or guidance text. Draft provisions have been prepared without prejudice to the form of the final instrument but on the assumption that the instrument would be a stand-alone legislative text.Rore than a decade ago, the Working Group in drafting the UNCITRAL Model Law on International Commercial Conciliation (2002) was not able to agree on a uniform way forward for the enforcement of iMSAs. This has been one of the main criticisms of the Model Law. So it is perhaps not surprising that the issue remains controversial. These four posts are written jointly with Nadja Alexander and Anna Howard to highlight the core concerns about the move towards a multilateral convention and the responses or counterarguments to those concerns. We focus on the legal form of a convention rather than a model law or guidance text as this focus allows us to be more specific in our comments. We have placed what seem to be the main concerns about the drive towards a convention into four categories, namely concerns relating to:1. the legitimacy of such a convention;2. the impact of such a convention on the objectives of, and values underpinning, the mediation process;3. the justifications for such a convention;4. the application of an arbitration enforcement framework to iMSAs particularly in light of recent trends in arbitration.This third post focuses on the justifications for a convention.